American literature from the 1850s to 1945 - Augustyn, Adam 1979- (Britannica guide to world literature., 2011)
Examines American literature that emerged after the mid-19th century, adopting a distinct realism and an often critical view of American society. Features writers such as Henry Adams and Upton Sinclair who exposed fundamental flaws in government and industry, while Mark Twain and H.L. Mencken incisively satirized social ills such as prejudice and intolerance.